Structural and dynamic insights into acyl carrier protein in Cutibacterium acnes reveal mechanisms for fatty acid synthesis and transport - Son, Minwon; Oh, Sujung; Oh, Yoojin; Cheon, Dasom; Jang, Ahjin; Kim, Eunhee; Kim, Nak-Kyoon; Kim, Yangmee (Academic Press, 2024)
Cutibacterium acnes thrives in anaerobic environments and plays a role in acne vulgaris and the emergence of antibiotic-resistant strains. To maintain membrane fluidity and protect against toxins under anaerobic conditions, C. acnes balances branched-chain fatty acids (BCFAs) and straight-chain fatty acids, produced by its fatty acid synthase. In this study, we investigated the molecular mechanisms of fatty acid synthesis in C. acnes by determining the first-solution structure and dynamics of the acyl carrier protein (CaACP) using NMR spectroscopy. Our analyses, integrating backbone dynamics and molecular dynamics simulations, revealed that CaACP contains two distinct subpockets that facilitate effective acyl chain transport, with critical residues-Met11, Ile46, and Cys50-regulating the binding cavity structure. Molecular dynamics simulations showed dynamic conformational changes within the protein, especially in the alpha 2 alpha 3 loop, influencing substrate entry and binding. These movements align with the backbone relaxation data, indicating a conformational exchange in residues Phe32, Val56, and Ile58. A structural switch involving the orientation of Met11 and Cys50 adjusts the acyl chain positioning within these subpockets, promoting the deep sequestration of long fatty acid chains and BCFAs. These insights advance our understanding of C. acnes' survival mechanisms and suggest potential therapeutic targets for combating antibiotic-resistant bacterial strains.